Analisis Dampak Revisi UU Mahkamah Konstitusi Terhadap Independensi Hakim Di Indonesia - M. Reza Saputra; Taufiqurrohman Syahuri (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze the revision of the Constitutional Court Law (UU MK) which has the potential to cripple the independence of judges and perpetuate authoritarian power in Indonesia. The research method used is critical analysis with a qualitative approach, which involves analysis of legal documents and related literature. This research reveals that the revision of the Constitutional Court Law could have a significant impact on the democratic system in Indonesia, with the risk of weakening the basic principles of the rule of law, separation of powers, and protection of citizens' constitutional rights. It is hoped that the research results will provide a comprehensive picture of the risks and impacts of the revision of the Constitutional Court Law and provide recommendations for strengthening the independence of the Constitutional Court and supporting the democratic system in Indonesia.